2007
DOI: 10.1124/jpet.106.116236
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Nerve Growth Factor Reverse Established Tactile Allodynia in Rodent Models of Neuropathic Pain without Tolerance

Abstract: A considerable body of evidence implicates endogenous nerve growth factor (NGF) in conditions in which pain is a prominent feature, including neuropathic pain. However, previous studies of NGF antagonism in animal models of neuropathic pain have examined only the prevention of hyperalgesia and allodynia after injury, whereas the more relevant issue is whether treatment can provide relief of established pain, particularly without tolerance. In the current work, we studied the effects of potent, neutralizing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 37 publications
(48 reference statements)
2
73
2
1
Order By: Relevance
“…might be used as a therapy for neuropathic pain (Ro et al, 1999;Wild et al, 2007). Indeed, algesia is a known side effect of systemic and local applications of NGF even in clinical trials (Apfel, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…might be used as a therapy for neuropathic pain (Ro et al, 1999;Wild et al, 2007). Indeed, algesia is a known side effect of systemic and local applications of NGF even in clinical trials (Apfel, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Wild et al reported that a single dose of anti-NGF antibody, injected intraperitoneally 7 days after spinal nerve ligation in rats, started to suppress allodynia on day 2 after injection, and this persisted to day 7 after injection (18). Conversely, a single dose of IPTRK3, injected intraperitoneally 7 days after the PSNL, started to suppress both thermal hyperalgesia and mechanical allodynia at 1 h after injection, and this persisted to day 2 after injection in the present study.…”
Section: Discussionmentioning
confidence: 40%
“…Peripheral nerve injury causing neuropathic pain increases NGF levels at peripheral sites (16,17). Intraperitoneal injection of either anti-NGF antibody or anti-TrkA antibody after peripheral nerve injury reportedly suppresses neuropathic pain in rodents (18,19). The present study showed that IPTRK3, a cellpenetrating peptide that inhibits TrkA activity, produced anti-allodynic and anti-hyperalgesia effects on neuropathic pain in mice.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…NGF-mediated effects are central to inflammatory, surgical, visceral and neuropathic pain (1,9,25,26). In developing dorsal root ganglion neurons NGF stimulates local synthesis of cAMP-response-element-binding protein, leading to retrograde transport to the neural soma (5).…”
Section: Introductionmentioning
confidence: 99%